Simulation of a heat pump system for total heat recovery from flue gas. (5th July 2015) - Wei, Maolin; Yuan, Weixing; Song, Zhijia; Fu, Lin; Zhang, Shigang
Abstract: This paper introduces an approach of using an open-cycle absorption heat pump (OAHP) for recovering waste heat from the flue gas of a gas boiler with a system model. And equivalent energy efficiency is used to evaluate two other heat recovery systems that integrate an electric compression heat pump (EHP) or an absorption heat pump (AHP) with a boiler. The key factors influencing the systems are evaluated. The OAHP system efficiency is improved by 11% compared to the base case. And the OAHP system is more efficient than the AHP or the EHP systems, especially when the solution mass flow rate is only a little less than the cold water mass flow rate. The energy efficiency comparison is supplemented with a simplified economic analysis. The results indicate that the OAHP system is the best choice for the current prices of electricity and natural gas in Beijing. Highlights: An OAHP system is analyzed to improve heat recovery from natural gas flue gas. OAHP system models are presented and analyzed. The key factors influencing the OAHP systems are analyzed. The OAHP system is most efficient for most cases compared with other systems. The OAHP system is more economic than other systems.